Intention to migrate : underlying factors affecting Malaysia brain drain - Mohd Safwan Ghazali; Muhammad Adidinizar Zia Ahmad Kusairee; Peck Leong Tan; Nurul Hafizah Mohd Yasin; Mohd Rushdan Yasoa (Faculty of Entrepreneurship and Business,UMK, 2015)
A high growth rate in the past have brought the country to its present state of being a middle income nation and has led to Malaysian skills professionals urging for better standard of living with better accommodation, better health care and other general needs which then have direct impacts onto the labour market. However, due to globalization, the mobility of labour has increased and this has encouraged them to seek for better opportunities outside their country of birth. This situation has created negative impacts to the sending countries such as shortage of skilled workers. Resulting from this, many skilled workers from the developing countries have been pitched to fill the shortage of skilled workers there. The phenomenon above is called brain drain which means that skilled workers tend to leave or work for other countries rather than their homeland. Brain drain is not only an issue in Malaysia itself but has been recognized globally. This will create an issue whether our talent pool can maintain equilibrium to support our robust industry growth or not. Hence, the objective of this study is alarming in terms of future migration of Malaysian youth talent pool and to discover the underlying factors influencing them to migrate. Subsequently, this study will involve Malaysian respondents who are currently studying abroad. The analyses will used are factorial analysis and Multiple Linear Regression Analysis. The expected results of this study are useful for the government through Talent Corporation to find out the effective solutions and strategies to retain our highly talented youth expertise.